2020
DOI: 10.1096/fj.202002178r
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial epithelial ARID1A is critical for uterine gland function in early pregnancy establishment

Abstract: Though endometriosis and infertility are clearly associated, the pathophysiological mechanism remains unclear. Previous work has linked endometrial ARID1A loss to endometriosis-related endometrial non-receptivity. Here, we show in mice that ARID1A binds and regulates transcription of the Foxa2 gene required for endometrial gland function. Uterine-specific deletion of Arid1a compromises gland development and diminishes Foxa2 and Lif expression. Deletion of Arid1a with Ltf-iCre in the adult mouse endometrial epi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Ltf iCre/+ Arid1a f/f mice are severely subfertile and exhibit implantation and decidualization defects at the peri-implantation and early post-implantation stages (GD 4.5–5.5), but the effects of endometrial epithelial Arid1a deletion on subsequent stages of pregnancy have not been previously reported [ 31 ]. We collected uterine samples at GD 7.5 and found that although the number of implantation sites was not different from controls (Control = 4.88 ± 1.47, Ltf iCre/+ Arid1a f/f = 5.00 ± 1.13, p = 0.8578), Ltf iCre/+ Arid1a f/f implantation sites were significantly decreased in diameter (Control = 3.80 ± 0.05 mm, Ltf iCre/+ Arid1a f/f = 2.89 ± 0.13 mm, p = 0.0002) and weight (Control = 0.0092 ± 0.0006 g, Ltf iCre/+ Arid1a f/f = 0.0060 ± 0.0004 g, p = 0.0092; Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ltf iCre/+ Arid1a f/f mice are severely subfertile and exhibit implantation and decidualization defects at the peri-implantation and early post-implantation stages (GD 4.5–5.5), but the effects of endometrial epithelial Arid1a deletion on subsequent stages of pregnancy have not been previously reported [ 31 ]. We collected uterine samples at GD 7.5 and found that although the number of implantation sites was not different from controls (Control = 4.88 ± 1.47, Ltf iCre/+ Arid1a f/f = 5.00 ± 1.13, p = 0.8578), Ltf iCre/+ Arid1a f/f implantation sites were significantly decreased in diameter (Control = 3.80 ± 0.05 mm, Ltf iCre/+ Arid1a f/f = 2.89 ± 0.13 mm, p = 0.0002) and weight (Control = 0.0092 ± 0.0006 g, Ltf iCre/+ Arid1a f/f = 0.0060 ± 0.0004 g, p = 0.0092; Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, studies using mouse models have shown that deletion of uterine Arid1a drives increased endometriosis-like lesion establishment and causes endometrial-factor infertility related to disrupted P4 and E2 signaling [ 22 , 24 , 28 ]. Focused study on the role of ARID1A in the endometrial epithelium has revealed its critical cell-type-specific roles of maintaining epithelial identity and enabling gland development and function in pregnancy [ 29 , 30 , 31 ]. Deletion of Arid1a in the adult mouse endometrial epithelium led to early pregnancy defects through attenuation of forkhead box A2 (FOXA2) expression and LIF secretion from uterine glands.…”
Section: Introductionmentioning
confidence: 99%
“…Progesterone regulates multiple endometrial epithelial cytokines involved in embryo implantation, including LIF. LIF expression appears to require ARID1A [12,13], whose deficiency results in defective or absent embryo implantation, persistence of ERa, and altered PR function. Interleukins 1 and 6 may also be involved in early implantation [14][15][16], but little relevant literature has been recently published.…”
Section: Mechanisms Governing Human Endometrial Receptivitymentioning
confidence: 99%
“…AT-rich interaction domain 1A (ARID1A) is a 250 kD switch/sucrose non-fermentable chromatin remodelling complex subunit with known tumour suppressor function and is associated with both endometriosis and orchestration of endometrial receptivity. 11 Intriguingly, ARID1A downregulation has been elaborated to be involved in the pathogenesis of endometriosis. 12 In this context, we speculated that the network of HDAC2, HNF4A and ARID1A might be correlated with the pathogenesis of endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between HNF4A and AT‐rich interactive domain 1A (ARID1A) has been rarely investigated, which warranted our research to study their relationship. AT‐rich interaction domain 1A (ARID1A) is a 250 kD switch/sucrose non‐fermentable chromatin remodelling complex subunit with known tumour suppressor function and is associated with both endometriosis and orchestration of endometrial receptivity 11 . Intriguingly, ARID1A downregulation has been elaborated to be involved in the pathogenesis of endometriosis 12 .…”
Section: Introductionmentioning
confidence: 99%